Paralysis caused by dinotefuran at environmental concentration via interfering the Ca2+–ROS–mitochondria pathway in Chironomus kiiensis - Wei, Fenghua; Gu, Weiwen; Zhang, Fengru; Wu, Shuangxin (Frontiers in Public Health, 2024)
Dinotefuran as the third-generation of neonicotinoid insecticides, is extensively used in agriculture worldwide, posing a potential toxic threat to non-target animals and humans. However, it is unclear that the chronic toxicity mechanism related to mitochondria damage of dinotefuran to non-target animals at environmental concentration. The objective of this study was to evaluate the chronic toxic effects and reveal the association between mitochondrial damage and behavioral inhibition. Our present study showed that chronic exposure to environmental concentrations of dinotefuran resulted in behavioral inhibition in the larvae of Chironomidae. For burrowing inhibition of 10-d, the lowest-observed-effect concentration (LOEC) and 50% inhibitory concentration (IC50) were 0.01 (0.01~0.04) and 0.60 (0.44~0.82) μg/L, respectively. Dinotefuran promoted the release of intracellular calcium ion (Ca 2+ ) in Chironomidae via dysregulating the gene expressions of atp2b, camk ii, and calm. ubsequently, the disruption of Ca 2+ signaling pathway induced oxidative stress by upraising reactive oxygen species (ROS), hydrogen peroxide (H2O2), and malonaldehyde (MDA) levels. Thus, the over-release of Ca 2+ and ROS disordered the normal functioning of mitochondrial-related pathway by dysregulating the expressions of mitochondria-related genes of atpef0a, sdha, and cyt b. Our findings showed that low environmental concentrations of dinotefuran caused paralysis of the midge via interfering Ca 2+ -ROS-mitochondria pathway. These results provided data support for assessing dinotefuran's potential environmental risk.